2010
DOI: 10.1175/2010jtecho730.1
|View full text |Cite
|
Sign up to set email alerts
|

Wind Speed Dependence of Single-Site Wave-Height Retrievals from High-Frequency Radars

Abstract: Wave-height observations derived from single-site high-frequency (HF) radar backscattered Doppler spectra are generally recognized to be less accurate than overlapping radar techniques but can provide significantly larger sampling regions. The larger available wave-sampling region may have important implications for observing system design. Comparison of HF radar-derived wave heights with acoustic Doppler profiler and buoy data revealed that the scale separation between the Bragg scattering waves and the peak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Also Wyatt (1986) and Wyatt et al (2006) have presented a method to invert Barrick et al's (1974) integral equation for the second-order cross section; it uses the measured second-order Doppler spectrum to estimate the ocean directional wave spectrum. More recently, Haus et al (2010) suggested a method to correct the bias in ocean wave height estimates from a single radar site introduced by the angle between the radio beam and wave direction.…”
Section: Wind Speed and Direction Estimation From Hf Radarsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also Wyatt (1986) and Wyatt et al (2006) have presented a method to invert Barrick et al's (1974) integral equation for the second-order cross section; it uses the measured second-order Doppler spectrum to estimate the ocean directional wave spectrum. More recently, Haus et al (2010) suggested a method to correct the bias in ocean wave height estimates from a single radar site introduced by the angle between the radio beam and wave direction.…”
Section: Wind Speed and Direction Estimation From Hf Radarsmentioning
confidence: 99%
“…HF radars can deliver real-time data at relatively high spatial resolutions (300-1500 m) and can be installed, operated, and maintained in all weather conditions at a reduced cost compared with satellite or in situ sensor technology. HF radars are used routinely to measure ocean surface currents (e.g., Barrick 1977b;Wyatt et al 2006;Parks et al 2009) , ocean wave spectra (e.g., Barrick 1977a, c;Wyatt 1986;Gurgel et al 2006;Haus et al 2010), and even wind direction (e.g., Heron and Rose 1986;Harlan and Georges 1994;Wyatt et al 2006). However, the measurement of wind speed still poses a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional validation studies of HF radar-derived waves are mainly based on comparison with fixed-point observations. This is because in situ devices have high precision and thus the evaluation results are generally reliable (Wyatt et al 1999(Wyatt et al , 2006Haus et al 2010;Long et al 2011;Lipa et al 2014;Atan et al 2016;Lorente et al 2018). However, an obvious limitation of this approach is that the comparison results are limited to only a few points (mostly in the sector of highprecision coverage) and they do not reflect the full spatial distribution of the accuracy of HF radarderived waves.…”
Section: Introductionmentioning
confidence: 99%
“…20c) where again sites N5 and N6 indicate a high broadening of the spectrum. It has been shown that the second-order spectra at large radar beam directions (.458) from the boresight, can be inaccurate due to signal contamination by sidelobe interference (Haus et al 2010). The calibration sites N4 and O2 have the lowest radial beam angles (,408), while all other sites are expected to be more susceptible to sidelobe interference.…”
Section: B Inverted Bulk Wave Parametersmentioning
confidence: 99%